Investigating the mechanisms of synaptic dysfunction in late-onset Alzheimer’s disease - Araújo, Margarida Nóbrega Campos de Freitas (2020)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2020